(untitled) (Law, State and Telecommunications Review, 2022)
[Purpose] The Internet of Things (IoT) has grown rapidly in the past few years and billions of devices are connected to the IoT network for collecting and sharing data globally for various applications. Due to the billions of connected devices, there is a potential risk of data loss, identity theft, device manipulation, trust issues, falsification of data, network/server manipulation, and various impacts in the application of IoT platforms. The IoT-enabled devices are growing rapidly day by day leading to amplify the threats to the reliability of the network. [Methodology/Approach/design] The research work aims to push the present state of the art by identifying privacy and security requirements that IoT is presently needed. [Findings] Various existing solutions for security in IoT and their limitations are addressed. Security issues such as trust based privacy policies for context-awareness, efficient holistic frameworks, and lightweight strategy for system resource constraints are identified. [Practical Implications] The technological age of IoT will be relying on a large number of devices is forecast to expand substantially. Although many of the technology-related privacy and security challenges exist, developers and researchers need to work in collaboration to resolve those threats, as they have accomplished with several other related technologies.